Perceptions about family-centred care among adult patients with chronic diseases at a general outpatient clinic in Nigeria - Kenneth Yakubu; Zelra Malan; Maria C. Colon-Gonzalez; Bob Mash (AOSIS, 2018)
Background: Few studies in Africa have described patients' perceptions about family-centred care (FCC). Aim: The aim of this study was to explore perceptions of FCC among patients with chronic diseases. Setting: The study was conducted at a general outpatient clinic (GOPC) in Jos, north-central Nigeria. Methods: We used a mixed-methods phenomenological study design and conducted structured and semi-structured interviews with 21 adult patients with chronic diseases at a general outpatient clinic in north-central Nigeria. Results: Patients described FCC using progressive levels of family engagement including the doctor inquiring about history of similar disease in the family, information sharing with family members and fostering of family ties. They described current family involvement in their care as either inquiring about their health, accompanying them to the clinic or offering material or social support and health advice. Also, patients considered the value of FCC based on how it meets information needs of the family, influences individual health behaviour and addresses family dynamics. Those who were literate and older than 50 years of age favoured FCC during history taking. Those who were literate, aged lesser than 50 years and had poor disease control showed preference for FCC during treatment decision-making. Conclusion: The acceptability of FCC is a complex synthesis of age, socio-economic status, literacy and disease outcomes. Patients older than 50 years, with good treatment outcomes, and those without formal education may need further education and counselling on this approach to care.